INVESTIGATION ON THE INTERACTION OF β-SITOSTEROL AND LUTEOLIN-7-GLUCOSIDE BINDING TO BOVINE SERUM ALBUMIN - GARAD, SUNIL VENKATRAO; SANGRAM PATIL, SIDHESHWAR (International Journal of Pharmacy and Pharmaceutical Sciences, 2023)
Objective: The study ondrug–protein interactions is an important field of interest because of the prospective of unraveling of drug action mechanisms and the possibility of designing novel medicines. Bovine serum albumin (BSA) has been studied extensively because of its structural homology with human serum albumin (HSA). The objective of the work was to study the interaction between β-sitosterol and Luteolin–7-glucoside with bovine serum albumin (BSA) investigated by molecular docking. Methods: Docking studies were carried out using a crystal structure of bovine serum albumin complexed with naproxen (pdb code-4OR0). Auto dock 4.2 was used to perform molecular docking. Ligands were found flexible during the docking process, and protein was kept rigid. Results: Molecular docking studies revealed that the β-sitosterol can bind in the large hydrophobic cavity of BSA, mainly by the hydrophobic interaction but also by hydrogen bond interactions between the hydroxyl (OH) group of β-sitosterol to SER 488 with hydrogen bond distance of 2.1Å. Luteolin-7-glucoside molecule interact by hydrophobic interaction with LYS 431, ARG 427, ALA 193 amino acids of Bovine Serum Albumin. The amino acids ARG 458, ARG 435, ARG 185 are involved in forming a hydrogen bond with hydroxyl oxygens, carbonyl carbon of Luteolin-7-glucoside with hydrogen bond distance of 2.4, 2.3 and 1.9 Å, respectively. Conclusion: Study indicated that hydrophobic and hydrogen bonding interactions were mostly responsible for albumin interaction. Further research of the pharmaceutical potential of plant molecules will be valuable for monitoring their biological functions.